Proposalls for an Act for the more speedy satisfaction of creditors, with little charge or trouble; of, and against such, as be of ability, and lye in prison and conceal their estates, wasting and consuming in a riotous and chargeable way, as much as would satisfie all, or a great part of that, which they owe to their creditors. With diverse proposals for necessary proviso's, for these and the former Proposals for an Act for setting at large prisoners for debt and damages not able to pay; and for saving to the people of this nation above three hund. thous. pounds yearly, by these proposals for creditors and prisoners. Diverse other proposals being ready to be published in convenient time (according as this receives encouragement) for the saving to this common-weal, fifteen hund. thous. pounds yearly, exacted from the people of this nation by unnecesary upstart officers, in innovated offices concerning the law, created without Parliament authority. / By Wil. Leach, of the middle Temple, Gent. [electronic resource] :
Summary goes here